HISTORY OF THE DEVELOPMENT OF BATAK-SPEAKING GMIM IN MANADO FROM 1970-2024: SEJARAH PERKEMBANGAN GMIM BERBAHASA BATAK DI MANADO DARI TAHUN 1970-2024 - Marcella Oktavia Pangkey; Evie Tumiwa (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This study examines the historical development of the GMIM Batak Language Congregation in Manado from 1970 to 2024. This phenomenon is unique because GMIM, founded in the Minahasa region, has opened itself to diverse ethnic groups, including the Batak community. Using a qualitative historical approach, the study reveals that Batak migrants who settled in Manado have made a significant contribution to the life of GMIM by preserving their language and culture in worship. The results show that the establishment and growth of GMIM Batak Language Congregation reflect cultural adaptation, unity in diversity, and the ecumenical spirit of GMIM. The study concludes that this congregation has not only enriched GMIM’s mission but also serves as a model of intercultural Christian fellowship in North Sulawesi.